2019
DOI: 10.1016/j.amc.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases spreading on a metapopulation network coupled with its second-neighbor network

Abstract: a b s t r a c tTraditional infectious diseases models on metapopulation networks focus on direct transportations (e.g., direct flights), ignoring the effect of indirect transportations. Based on global aviation network, we turn the problem of indirect flights into a question of second neighbors, and propose a susceptible-infectious-susceptible model to study disease transmission on a connected metapopulation network coupled with its second-neighbor network (SNN). We calculate the basic reproduction number, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The effect of nodal communities on superspreader risk merits further research. In addition, future analysis should consider the case in which movement between adjacent nodes is not symmetric, which would require a directed network graph structure for the metapopulation network, as well as networks with multiple layers of mobility [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of nodal communities on superspreader risk merits further research. In addition, future analysis should consider the case in which movement between adjacent nodes is not symmetric, which would require a directed network graph structure for the metapopulation network, as well as networks with multiple layers of mobility [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on passenger flights between locations can help to track ZIKV spread, 29 , 39 , 40 but limit our understanding of movement to the origin and destination airports and rarely considers connections made between flights and travel made at the individual level. 53 Call data records from mobile phones offer large coverage of populations and areas and can be leveraged to measure individual-level movement in near real time. 22 , 52 Access to call data records is currently restricted to research groups and access is granted via a negotiated agreement with the operator, which makes their widespread use challenging.…”
Section: Using Human Mobility To Model Zikv Spreadmentioning
confidence: 99%
“…Their work lays a foundation for future researches on metapopulation networks. From the point of view of network structure, Cao et al studied the rendezvous effects on bipartite metapopulation network and found that rendezvous effects made for the transmission of infectious diseases [3] ; Liu et al investigated time-varying metapopulation networks, which slowed down the spread of infectious diseases [4] ; Mata et al studied local subpopulation structure on metapopulation networks, that is, individuals within a subpopulation were not well-mixed but within a social network [5] ; we defined a second-neighbor network (SNN) and investigated the global spread of infectious disease on a metapopulation network coupled with its SNN [6] . In order to avoid being infected, individuals may respond to infectious diseases.…”
Section: Introductionmentioning
confidence: 99%